Numerical calculations of elastic constants of sedimentary strata in triclinic approximation based on vertical seismic profiling data - G.T. Prodayvoda; P. Kuzmenko; A. Vyzhva (Геофизический журнал, 2015)
It has been firstly determined the symmetry and complete component set of tensor matrix of elastic constants and elastic compliances by inversion of radial velocity indicatrices for quasi-longitudinal, "quick" and "slow" quasi-transverse waves that are obtained according to the VSP method in the standard acoustic coordinate system. It was established that the elastic constants of clay strata have planar triclinic symmetry and carbonate strata have axial rhombic symmetry. The value of the elastic anisotropy integral coefficient is nearly 22 %. Longitudinal axis and acoustic normal of sedimentary strata were firstly determined according to field seismic survey. The estimation errors of elastic symmetry approximation for sedimentary strata by models with transversely isotropic and orthorhombic symmetry were calculated. It is proved that such approximation significantly changes the nature of the seismic wave azimuthal anisotropy and causes high error, which can significantly reduce the 3D seismic efficiency to the oil and gas exploration in the complex geological conditions.